The relationship of knowledge sharing behavior towards the organizational innovation capability (case study of ISP organization in Malaysia) - Hassad, Hassan (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis.